Procesos microbianos y actividades humanas relacionados con problemas de insostenibilidad : Revisión sistemática 2005-2012 (2016)
ABSTRACT: the problems of unsustainability are social-ecological issues. The study of this kind of problems requires contributions from different disciplines such as microbiology. Methods: this systematic review of the literature was aimed at describing problems of unsustainability tackled by microbiology, as well as the microbial processes and human activities related to them. Results: the results indicate that studies on microbiology focus mainly on two problems, namely, farmland degradation and depletion, and energy sources depletion. In this context, the microbial processes that seem to be more important are nutrient recycling, and lipid and hydrogen production. Conclusion: the human activities explored to study these processes are crop management practices, biofertilizer use and production, and biofuel production.